Soberanía de semillas campesinas y justicia climática en un mundo biotecnológico - Hernández Rodríguez, Carol (2023)
Peasant agriculture and its agrobiodiversity systems are at a juncture in which two global processes impose significant challenges for their sustainability: climate change and the expansion of agricultural biotechnology supported by a regimen of intellectual property rights over plant genetic resources. In this article, I explore some potential risks these global processes impose on peasant agriculture, particularly on their seed systems. We analyze how, in response, peasant communities have increasingly mobilized around two converging political agendas, seed sovereignty and climate justice. In addition to the political achievements confronting some of the great biotechnology and corporate developments in the context of climate change, community peasant actions implemented to protect and defend their seeds directly contribute to reaffirming peasant seeds as part of peoples’ commons and preserving the diversity of the plant genetic resources hold in their hands, which may be vital for the adaptation of peasant food systems to future climate scenarios.